THE USE OF ZEOLITE CLAY TO PRODUCE A SOLID POTTERY OBJECT - Mohammed Hamdan Shamkhi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research includes the use of a natural raw material available in Iraq, which is the Iraqi Zeolite clay, this kind of clay exists in Al Najaf area specifically within Bahr Al-Najaf in the production of a strong and solid pottery objects that can be used in ceramic artistic products, where the effect of some additives on the properties of Zeolite has been diagnosed, which can lead to future technical and industrial applications of the country, three models of Zeolite clay have been prepared in proportions (90% - 80% - 70%) with two types of additives: Iraqi Kaolin clay (Kaolin) found in the Western Sahara of Iraq and sodium carbonate. (Na2CO2), the samples were burned at temperatures (1000-1100-1200 C). Several properties were studied in this research, including the test of shrinkage after heating and fracture resistance and compressive strength. It was found that the addition of Kaolin and sodium carbonate improves the qualities of the Zeolite clay, since Kaolin clay has a high density and few pores, when added to the Zeolite of low density due to the large number of pores and its large size, it modified the qualities of Zeolite, as well as the sodium carbonate has melted the bonds that shape Zeolite and made it possible to produce a solid clay object that could be used in ceramic and art products.